1997
DOI: 10.1093/protein/10.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the G-protein-coupled neuropeptide Y Y1 receptor agonist and antagonist binding sites

Abstract: Neuropeptide Y (NPY) receptors belong to the G-protein-coupled receptor (GPCR) superfamily and mediate several physiological responses, such as blood pressure, food intake, sedation and memory retention. To understand the interactions between the NPY Y1 receptor subtype and its ligands, computer modeling was applied to the natural peptide agonist, NPY and a small molecule antagonist, BIBP3226. An agonist and antagonist binding domain was elucidated using mutagenesis data for the Y1 receptor as well as for othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 19 publications
6
46
2
Order By: Relevance
“…In contrast, a few other investigators have found that peptide agonists and peptide or nonpeptidic antagonists have overlapping binding sites on their receptors, including the B 2 bradykinin (43), the ␤-adrenergic (44), the cholecystokinin (45), and the neuropeptide Y Y1 receptors (46). These differences may be attributed to elucidation of only a subset out of multiple interaction sites between ligand and receptor, especially in the case of intermediate-size peptide ligands.…”
Section: Contact Sites Of a Pthrp Agonist And An Antagonistmentioning
confidence: 98%
“…In contrast, a few other investigators have found that peptide agonists and peptide or nonpeptidic antagonists have overlapping binding sites on their receptors, including the B 2 bradykinin (43), the ␤-adrenergic (44), the cholecystokinin (45), and the neuropeptide Y Y1 receptors (46). These differences may be attributed to elucidation of only a subset out of multiple interaction sites between ligand and receptor, especially in the case of intermediate-size peptide ligands.…”
Section: Contact Sites Of a Pthrp Agonist And An Antagonistmentioning
confidence: 98%
“…The antagonist binding site at the Y 1 -receptor has been investigated by the combination of sitedirected mutagenesis and molecular modeling studies (Plate 1) [57,73]. The finding that a large number of mutants maintained affinity for both NPY and BIBP3226, or lost it for both of them, suggests the presence of an overlapping binding site of the agonist and the antagonist.…”
Section: Antagonistsmentioning
confidence: 99%
“…The NMS and Ach binding sites overlap in that the cationic headgroups of NMS and Ach bind within the same charge-stabilized aromatic cage of the receptor, but Ach has a compact acetoxy side chain and cannot replicate the stabilizing interhelical interactions provided by the bulky side-chains of NMS (for review, see Lu et al, 2002). In the neuropeptide Y (NPY) receptor, the 36-amino acid C-terminal amidated neuropeptide NPY and a small nonpeptide NPY1 antagonist, BIBP3226, seem to share residues for interactions within the transmembrane regions of the receptor, including Gln-120 (3.32), Asn-283 (6.55), and His-306 (7.39), which are in the same position of key residues for ligand binding of other peptide and biogenic amine receptors (Du et al, 1997).…”
Section: Discussionmentioning
confidence: 99%